Development of Educational Technology from the Qur'an Perspective: Perkembangan Teknologi Pendidikan dalam Perspektif Al-Qur’an - Mu'minin, Nasrul; Nurmala, Eka; Sabaruddin; Sultan; Hartati, Diah Vitaloka (PT. Alpha Trianguli Australis, 2024)
This Islam has determined that the state is tasked with regulating the entire education system so that it can be accessed and obtained easily by the people. The Qur'an emphasizes the importance of observing and contemplating existing natural phenomena. This research aims to determine the development of educational technology from the perspective of the Qur'an. This research uses the library research method. The technique used in collecting data in this research is by searching for literature in the form of articles or journal publications available via the web (internet) or manually. The development of science and technology has existed since the time of the Prophet, even before the Prophet Muhammad SAW. The Qur'an has discussed and explained knowledge and technology, including surah Al-Baqarah (2): 31, surah At-Taubah (9): 122, surah Al-Mujadilah (58): 11, surah Al-’Alaq (96): 1-5, surah Al-Jatsyiah (45): 13, surah Al-Anbiya (21): 80-81, surah Yasin (36): 41-42, and surah Al-Fiil (105): 1-5.